Well done the naughtiest girl! - "Blyton , Enid" (Hodder Childrens books: London, 1999)
Jo, Bessie and Fanny are fed up when Connie comes to stay - she's so bossy. But they don't let her stop them having fun with their magical tree friends Silky, Moon-Face and the Saucepan Man. Together the climb through the cloud to the magical lands - and Connie learns to behave herself.
Keywords: Fantasy fiction